2019
DOI: 10.3390/pharmaceutics11120644
|View full text |Cite
|
Sign up to set email alerts
|

Development and In Vivo Evaluation of Multidrug Ultradeformable Vesicles for the Treatment of Skin Inflammation

Abstract: The aim of this work was to evaluate the effect of two chemically different edge activators, i.e., Tween® 80 and sodium deoxycholate, on (i) the physical, mechanical, and biological properties of ultradeformable vesicles, and (ii) the administration of naproxen sodium-loaded multidrug ultradeformable vesicles for the transdermal route in order to obtain therapeutically meaningful drug concentrations in the target tissues and to potentiate its anti-inflammatory effect by association with the antioxidant drug id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The stability of the nanostructures containing the anticancer drug at room temperature (20 °C) and at body temperature (37 °C) was also investigated by means of a Turbiscan Lab ® Expert apparatus, which is able to correlate the transmittance and backscattering of a formulation as a function of time and temperature [ 40 , 41 ]. The resulting data confirmed that the encapsulation of the active compound did not induce any significant variation in the TSI profiles at room temperature in both nanosystems as compared to the empty formulations, suggesting that the nanostructures effectively retain the drug with no destabilizing phenomena across time ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The stability of the nanostructures containing the anticancer drug at room temperature (20 °C) and at body temperature (37 °C) was also investigated by means of a Turbiscan Lab ® Expert apparatus, which is able to correlate the transmittance and backscattering of a formulation as a function of time and temperature [ 40 , 41 ]. The resulting data confirmed that the encapsulation of the active compound did not induce any significant variation in the TSI profiles at room temperature in both nanosystems as compared to the empty formulations, suggesting that the nanostructures effectively retain the drug with no destabilizing phenomena across time ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The in vivo applicability of emulsions containing ferulic acid was evaluated using a non-invasive method [ 34 ]. The study involved 12 healthy human volunteers (both sexes) with a mean age of 31 ± 5 years, who provided their written and informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The various measurements were carried out in triplicate on three different batches (each one of 10 determination). Results were expressed as the mean of three measurements ± standard deviation [ 23 ].…”
Section: Methodsmentioning
confidence: 99%